Research on synthesis and property of anti-clay polycarboxylate superplasticizer. Issue 1 (July 2020) - Xiong, Qiumin; Chen, Xiaobin; Dang, Wei; Guo, Xiujuan; Xu, Han; Li, Guangzhou; Guan, Jican; Huang, Xiaohu
Abstract: With isopentenyl polyoxyethylene polyether (TPEG), maleic anhydride (MAH), acrylic acid (AA) and binary ester (DBE) as monomers, hydrogen peroxide (H2 O2 ) as initiator and mercaptoacetic acid (MAA) as chain transfer agent, the anti-clay polycarboxylate superplasticizer (APC) was synthesized. The structure of polymer was characterized by infrared spectroscopy (FTIR) and gel permeation chromatography (GPC). The fluidity of cement paste mixed with montmorillonite (MMT) and the slump of concrete were used as evaluation indicators to investigate its mud resistance and dispersion properties. The results showed that when the content of bentonite (MMT) in the cement was 3% and the content of APC was 0.15% of the cement quality, the initial fluidity of the cement paste was 235 mm and the fluidity in 2 hours was 187 mm. The concrete test was carried out with the machine-made sand with high mud content: the slump flow was 560 mm, and the slump flow was 500 mm after 2 hours. APC has good mud resistance and good dispersion and retention properties.